2021
DOI: 10.1038/s41598-021-87961-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic associations of cardiac abnormalities among hospitalized patients with COVID-19: a systematic review and meta-analysis

Abstract: Although most patients recover from COVID-19, it has been linked to cardiac, pulmonary, and neurologic complications. Despite not having formal criteria for its diagnosis, COVID-19 associated cardiomyopathy has been observed in several studies through biomarkers and imaging. This study aims to estimate the proportion of COVID-19 patients with cardiac abnormalities and to determine the association between the cardiac abnormalities in COVID-19 patients and disease severity and mortality. Observational studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Our meta-analysis of 16,791 samples suggests that increased cardiac biomarkers at admission in patients with COVID-19 infection are related to increased risk of disease and death. The present study’s findings of increase in mortality and severity risk among COVID-19 patients with cardiac abnormality biomarkers test are consistent with previous narrative reviews [ 9 , [74] , [75] , [76] ].…”
Section: Discussionsupporting
confidence: 92%
“…Our meta-analysis of 16,791 samples suggests that increased cardiac biomarkers at admission in patients with COVID-19 infection are related to increased risk of disease and death. The present study’s findings of increase in mortality and severity risk among COVID-19 patients with cardiac abnormality biomarkers test are consistent with previous narrative reviews [ 9 , [74] , [75] , [76] ].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the present findings are in keeping with recent reports that patients with cardiovascular comorbidities are more likely to develop an adverse course due to SARS-Cov-2 infection [8][9][10][11][12] and support aggressive and systematic implementation of SARS-Cov-2 prophylaxis and management options in HCM patients, particularly in the presence of high-risk features.…”
Section: Characteristics Of Hcm Patients Experiencing Adverse Sars-co...supporting
confidence: 91%
“…Several systematic reviews found the predictors of severity and lethality in COVID-19 non-Brazilian patients. [6][7][8][10][11][12] Our findings in a Brazilian population are in accordance with such studies. In a systematic review by Harrison et al, CKD was the strongest predictor of higher lethality and severe disease (OR 3.07, 95%CI 2.43-3.88), followed by diabetes mellitus (OR 2.09, 95%CI 1.8-2.42) and hypertension (OR 2.5, 95%CI 2.02-3.11).…”
Section: Discussionsupporting
confidence: 92%
“…4,5 The cardiovascular impact of COVID-19 in patients has recently been confirmed in several large studies from different parts of the world. [6][7][8][9][10][11][12] Furthermore, patients with COVID-19 may…”
mentioning
confidence: 99%